2018
DOI: 10.1111/bjdp.12270
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adolescent and parent reports of externalizing problems: A longitudinal population‐based study

Abstract: Adolescent and parent reports of adolescent mental health problems often correlate poorly, and understanding this discrepancy has clinical importance. Yet contextual factors have only been inconsistently explained. At the 14-and 17-year follow-ups of the Western Australian Pregnancy Cohort (Raine) Study, 1,596 parent-child dyads completed the parent-reported Child Behaviour Checklist (CBCL) and the adolescent-rated Youth Self-Report (YSR). Maternal, family, adolescent, and parent factors were examined as poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
1
10
1
2
Order By: Relevance
“…To the best of our knowledge, this is the first report on the prevalence of mental health problems in a general population sample aged 14-18 in Italy. Compared to previous international research that reports a prevalence of clinical Total Problems between 11% and 27% (Philipp et al, 2018;Robinson et al, 2018), our findings provide evidence of a higher prevalence of mental health problems in adolescence, with, in particular, a high prevalence of Internalizing Problems. The only previous Italian report is the PrISMA study, reporting a prevalence of 9.8% of mental disorders assessed with the child behavior checklist (CBCL/6-18) on 3418 pre-adolescents (10-14 years old) (Frigerio et al, 2009).…”
Section: Prevalence Of Beepscontrasting
confidence: 70%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report on the prevalence of mental health problems in a general population sample aged 14-18 in Italy. Compared to previous international research that reports a prevalence of clinical Total Problems between 11% and 27% (Philipp et al, 2018;Robinson et al, 2018), our findings provide evidence of a higher prevalence of mental health problems in adolescence, with, in particular, a high prevalence of Internalizing Problems. The only previous Italian report is the PrISMA study, reporting a prevalence of 9.8% of mental disorders assessed with the child behavior checklist (CBCL/6-18) on 3418 pre-adolescents (10-14 years old) (Frigerio et al, 2009).…”
Section: Prevalence Of Beepscontrasting
confidence: 70%
“…Verhulst and colleagues (Verhulst, Prince, Vervuurt-Poot, & de Jong, 1989) found a small age effect on Total Problem score with girls scoring higher with increasing age. In an Australian sample ( N = 1754), the prevalence of clinical Total Problem raised between age 14 and 17 from 11.7% in boys and 13.0% in girls to 13.0% and 19.3%, respectively (Robinson et al, 2018). Achenbach et al (1987), Fitzpatrick & Deehan (1999) and Verhulst et al (1989) found no age effect on Total problems.…”
Section: Discussionmentioning
confidence: 99%
“…A crossover effect might also result in a compensation effect, such that parental reports on own scores are reduced by the views or experiences of the secondary caregiver. Thus, future studies may investigate parenting and child outcomes from a more family systems perspective by including other family members, including other children in the household (Richmond et al, 2005;Robinson et al, 2019), as well. A final limitation to mention is that we were unable to investigate full bidirectionality from age 9 months to 9 years, due to missing information about child behavior when the child was 9 months old.…”
Section: Discussionmentioning
confidence: 99%
“…Em uma pesquisa com adolescentes espanhóis observou-se associação clara entre PI (passividade, apatia, depressão, entre outras manifestações) e um estilo parental autoritário. (Robinson et al, 2019). Chen et al (2017), em pesquisa realizada sobre discrepâncias entre relatos de pais e filhos sobre PEC de adolescentes, em Taiwan, encontraram concordância moderada em uma amostra de 1.412 pares de pais e adolescentes, chegando a refutar a hipótese de que sociedades com fortes tradições de familismo e coletivismo teriam maior concordância entre pais e filhos, sendo o termo familismo utilizado para designar uma ideologia do oriente que prioriza a família.…”
Section: Discussionunclassified
“…Tambémforam relatados níveis inadequados de afeto, com predomínio de agressão e rejeição, associada à expressão de PE (agressividade, hostilidade e delinqüência). Neste estudo espanhol também foi sugerido que carinho insuficiente recebido da mãe combinado com rejeição pelo pai esteve associado a maior probabilidade do filho desempenhar papel de agressor no ambiente escolar(Ortuño-Sierra et al, 2017).Um importante estudo longitudinal realizado na Austrália porRobinson et al (2019), sobre os relatos de adolescentes e pais sobre saúde mental de adolescentes, observou-se baixa correlação e o entendimento desta discrepância tem importância clínica. Em acompanhamentos de 14 e 17 anos do Estudo da Coorte de Gravidez da Austrália Ocidental, 1.596 díades de pais e filhos completaram o CBCL relatada pelos pais e o YSR pelos jovens.…”
unclassified